Developing An Authentic Assessment Instruments of Psychomotor Domain For The Physics Learning on Measurement Materials in Class X SMA - Dahlia Dahlia; Maison Maison; Nehru Nehru (Journal of Science Education Research, 2020)
Practicum is a form of learning activity relates to assessment, which is part of a series of learning processes. Assessment in practicum not only consists of cognitive aspects but also emphasizes affective and psychomotor aspects. Psychomotor is a domain related to skills or ability to act after receiving learning experiences. An authentic assessment of the psychomotor domain is needed to determine each student learns and apply their learning outcomes into life. The study aimed to determine the procedure for developing an authentic assessment instrument of the psychomotor domain for physics learning on measurement material in class X SMA and describe the teacher's assessment toward the developed the authentic assessment instrument. The study used Dick and Carey developmental model consisted of ten stages. They are (1) analysis the learning objectives, (2) learning analysis, (3) analysis of students and their environment, (4) formulating specific objectives, (5) developing assessment instruments, (6) developing learning strategy, (7) developing and selecting learning materials, (8) formative evaluation, (9) revision, and (10) summative evaluation. But, the article used only nine of ten stages. The validation sheet was assessed by two expert lecturers. The product of the psychomotor assessment instrument was validated by two expert lecturers through 2 revisions. The developed instrument was tested in small groups, namely class X MIA 7, SMA N 1 Muaro Jambi. The validation obtained a total score of 136. Means, the score included in the category of 136 less than or equal to N less than 150: "Very Good." The teacher's responses were 82% of very good (positive). In short, the developed instrument was feasible to continue to trial steps. The trial to 10 students obtained a mean of 82.1. Based on the range of student scores, seven students were classified as highly skilled, and three students were classified as skilled. Based on results and discussion, it concluded that authentic assessment instruments of the psychomotor domain for the physics learning on measurement materials were feasible to use for teacher class of class X MIA in SMA N 1 Muaro Jambi.